Playing position, height, weight, and preferred throwing arm do not differentiate between more and less effective 7- metre throwers at the highest level of international handball - Laxdal, A.; Haugen, T. (International Journal of Performance Analysis in Sport, 2026)
The aim of this study was to evaluate what characterised the best 7 m throwers in elite handball. The 7 m throwing records of 95 males and 104 females who collectively took 12,033 7 m throws at the 43 major championships (European Championship, World Championship, and Olympics) from 2007-2024 were studied. This was done to assess whether some characteristics set the best throwers apart from those who were less successful. A multinomial logistic regression found no significant differences between the 7 m throwers on a range of characteristics. These findings indicate that the variability within each characteristic is as great as the variability between characteristics. What makes the different 7 m throwers efficient from the 7 m line does therefore appear less important than the fact that something makes them efficient from the 7 m line.